Agnes high, Western Desert, Egypt: A structural study in view of potential data modelling - A.A. Azab (Egyptian Journal of Petroleum)
The spatial relationship between the gravity and magnetic maxima of Agnes horst had been studied utilizing a joint modelling technique. The process depends mainly upon combining the Bouguer and Reduced To north Pole (RTP) aeromagnetic data for constructing 2D/2.5D models of the upper crustal layers. These integrated approaches were accomplished in regional and shallow senses along two profiles, for better obtaining source parameters and finding out the structural style. Results of the qualitative analysis show that Agnes high gravity and magnetic association is mainly caused by a near surface igneous intrusion of NW orientation. Quantitatively, regional models indicate a normal continental type of crust, which is divided into upper and lower by the Conrad surface (21.5–22 km). The crust–mantle interface lies at 32–33 km meanwhile the magnetic crust reaches a depth of 16 km. Local models reveal that the basement rocks north and south of the Agnes high were offset by some 6–8 km and 3–4.5 km, respectively. Statistically, the area was controlled by two main old trends; the most prevailing WNW to NNW (East African) and the less abundant ENE (Syrian Arc) trends. These two principal trends almost have its doubtless impact on preservation of possible accumulations.